2012
DOI: 10.1007/s15010-012-0385-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus and hepatitis A virus exposures in an apparently healthy high-risk population in Italy

Abstract: Compared to the general population, significantly higher anti-HEV and anti-HAV prevalences were observed in an inmates population in Italy. Old age and non-Italian nationality were factors independently related to both HEV and HAV exposures. This data suggest the important role of low socio-economic factors in the transmission of both infections in high-risk populations. The possible epidemiological and/or pathogenetic links between HEV and HIV exposures need to be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 38 publications
8
27
0
Order By: Relevance
“…As in previous studies, we found an association of presence of antibodies against HEV and age ( 1 , 6 ). Higher prevalence among older PWID suggests that there may be age-related exposures independent of injection drug use that increases the likelihood of HEV infection.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As in previous studies, we found an association of presence of antibodies against HEV and age ( 1 , 6 ). Higher prevalence among older PWID suggests that there may be age-related exposures independent of injection drug use that increases the likelihood of HEV infection.…”
Section: Discussionsupporting
confidence: 90%
“…Because of the common mode of fecal–oral transmission of HAV and HEV, other studies have also investigated an association between HAV and HEV infections, but results have been inconclusive ( 1 , 5 , 6 ). As in previous studies, we found an association of presence of antibodies against HEV and age ( 1 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also previously shown in many other studies. In most of the countries also the HAV seroprevalence was higher than the HEV seroprevalence, in similar age groups [3640]. …”
Section: Discussionmentioning
confidence: 99%
“…In 1990-1991, the etiological agent of such outbreaks was isolated, partially cloned and was labeled hepatitis E virus [28]. HEV is now considered the leading cause of enterically transmitted non-A hepatitis in low socio-economic communities [29] and is considered endemic in developing countries. In these outbreaks, the severe infection during pregnancy maybe linked to the greater virulence of HEV-1 genotype and the genetic repertoire of Asian populations [8].…”
Section: Mode(s) Of Transmission and Endemicitymentioning
confidence: 99%